Pattern of Progression after Stereotactic Body Radiotherapy for Oligometastatic Prostate Cancer Nodal Recurrences. Issue 9 (September 2016) - Ost, P.; Jereczek-Fossa, B.A.; Van As, N.; Zilli, T.; Tree, A.; Henderson, D.; Orecchia, R.; Casamassima, F.; Surgo, A.; Miralbell, R.; De Meerleer, G.
Abstract: Aims: To report the relapse pattern of stereotactic body radiotherapy (SBRT) for oligorecurrent nodal prostate cancer (PCa). Materials and methods: PCa patients with ≤3 lymph nodes (N1/M1a) at the time of recurrence were treated with SBRT. SBRT was defined as a radiotherapy dose of at least 5 Gy per fraction to a biological effective dose of at least 80 Gy to all metastatic sites. Distant progression-free survival was defined as the time interval between the first day of SBRT and appearance of new metastatic lesions, outside the high-dose region. Relapses after SBRT were recorded and compared with the initially treated site. Secondary end points were local control, time to palliative androgen deprivation therapy and toxicity scored using the Common Terminology Criteria for Adverse Events v4.0. Results: Overall, 89 metastases were treated in 72 patients. The median distant progression-free survival was 21 months (95% confidence interval 16–25 months) with 88% of patients having ≤3 metastases at the time of progression. The median time from first SBRT to the start of palliative androgen deprivation therapy was 44 months (95% confidence interval 17–70 months). Most relapses (68%) occurred in nodal regions. Relapses after pelvic nodal SBRT ( n = 36) were located in the pelvis ( n = 14), retroperitoneum ( n = 1), pelvis and retroperitoneum ( n = 8) or in non-nodal regions ( n = 13). Relapses after SBRT for extrapelvic nodes ( n = 5) were located in the pelvis ( n = 1) or the pelvis and retroperitoneum ( n = 4). Late grade 1 and 2 toxicity was observed in 17% ( n = 12) and 4% of patients ( n = 3). Conclusion: SBRT for oligometastatic PCa nodal recurrences is safe. Most subsequent relapses are again nodal and oligometastatic. Highlights: SBRT for oligometastatic prostate cancer nodal recurrence is safe. Relapses after SBRT are often nodal and limited in number. The median disease-free interval after SBRT is 21 months.